High‐Resolution Electron Tomography of Ultrathin Boerdijk–Coxeter–Bernal Nanowire Enabled by Superthin Metal Surface Coating. Issue 41 (9th September 2022) - Song, Xiaohui; Zhang, Xingyu; Chang, Qiang; Yao, Xin; Li, Mufan; Zhang, Ruopeng; Liu, Xiaotao; Song, Chengyu; Ng, Yun Xin Angel; Ang, Edison Huixiang; Ou, Zihao
Abstract: The rapid advancement of transmission electron microscopy has resulted in revolutions in a variety of fields, including physics, chemistry, and materials science. With single‐atom resolution, 3D information of each atom in nanoparticles is revealed, while 4D electron tomography is shown to capture the atomic structural kinetics in metal nanoparticles after phase transformation. Quantitative measurements of physical and chemical properties such as chemical coordination, defects, dislocation, and local strain have been made. However, due to the incompatibility of high dose rate with other ultrathin morphologies, such as nanowires, atomic electron tomography has been primarily limited to quasi‐spherical nanoparticles. Herein, the 3D atomic structure of a complex core–shell nanowire composed of an ultrathin Boerdijk–Coxeter–Bernal (BCB) core nanowire and a noble metal thin layer shell deposited on the BCB nanowire surface is discovered. Furthermore, it is demonstrated that a new superthin noble metal layer deposition on an ultrathin BCB nanowire could mitigate electron beam damage using an in situ transmission electron microscope and atomic resolution electron tomography. The colloidal coating method developed for electron tomography can be broadly applied to protect the ultrathin nanomaterials from electron beam damage, benefiting both the advanced material characterizations and enabling fundamental in situ mechanistic studies. Abstract : Here, the atomic resolution electron tomography (AET) is enriched by resolving ultrathin Boerdijk–Coxeter–Bernal nanowire morphology damage under electron beam irradiation via surface coating strategy. Furthermore, for the first time, surface coating in colloidal, in situ transmission electron microscopy imaging, and AET have been combined to reveal the core–shell nanowire stability and composition in atomic resolution.